Learner Support Services for Online Students: Scaffolding for success - Ludwig-Hardman, Stacey; Dunlap, Joanna C. (International Review of Research in Open and Distributed Learning, 2003)
A critical component of an effective retention program for online students is a learner support services program. While many factors contribute to attrition, at the top of the list are level of interaction and support. To this end, some students in distance learning programs and courses report feelings of isolation, lack of self-direction and management, and eventual decrease in motivation levels. This article describes the types of learner support services strategies that can effectively address these retention challenges. Examples from Western Governors University (WGU) are provided to describe these strategies in action.